2022
DOI: 10.1108/jarhe-02-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of financial stress among university students and its impact on their performance

Abstract: PurposeTo identify the financial stress and associate factors of tertiary level student.Design/methodology/approachTo identify the financial stress and associate factors, a structured questionnaire was developed to collect data from 571 students of different universities of Bangladesh through Google form. Chi square and Cramer's V were applied to find the associated factors with financial stress of students, whereas ordinal regression was performed to evaluate the influence of the associated factors on financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…This particular study shows that a student's participation in various academic and extracurricular activities is impacted by financial stress. As a result, the component to assess students' stress should be taken into account by parents, university administration, and student counselors (Hossain et al, 2023). Stress has an emotional impact that may show up as anger or aggression, a sense of being out of control, insomnia, weariness or fatigue, sadness or sorrow, memory or concentration issues, or other symptoms (Racine, 2020).…”
Section: Discussionmentioning
confidence: 99%

How do Student Leaders in a Teachers’ College Cope with Stress?

John Erwin Prado Pedroso,
Timothy Christian Bonyog,
Renee Mae Hinojales
et al. 2023
JSSMS
“…This particular study shows that a student's participation in various academic and extracurricular activities is impacted by financial stress. As a result, the component to assess students' stress should be taken into account by parents, university administration, and student counselors (Hossain et al, 2023). Stress has an emotional impact that may show up as anger or aggression, a sense of being out of control, insomnia, weariness or fatigue, sadness or sorrow, memory or concentration issues, or other symptoms (Racine, 2020).…”
Section: Discussionmentioning
confidence: 99%

How do Student Leaders in a Teachers’ College Cope with Stress?

John Erwin Prado Pedroso,
Timothy Christian Bonyog,
Renee Mae Hinojales
et al. 2023
JSSMS
“…For example, Appel and Dahlgren (2003) conducted a mixed-method study to investigate the financial obstacles encountered by Swedish doctoral students in their doctoral programs. Furthermore, another study also discussed the importance of financial stress on university students' performance in Bangladesh (Hossain et al, 2022). Hence, prior literature has little discussion on anxiety and stress on doctoral students' performance through self-regulated learning, which needs to be explored in the present study.…”
Section: Students' Challenges In the Doctoral Program Around The Globementioning
confidence: 95%
“…The results indicated that their stress stemmed from mastering a new language and adapting to a new culture and academic environment. So, stress proved to be a source of the declined work performance of doctoral students (Ganley et al, 2021;Hensley et al, 2021;Hossain et al, 2022).…”
Section: The Mediating Role Of Self-regulated Learningmentioning
confidence: 99%
“…Many students grapple with the weight of tuition fees, living expenses, and other financial obligations. Additionally, the constant comparison between the cost of their education and their academic performance can compound this stress (Hossain et al, 2022). Secondly, peer pressure, emanating from both neighbors and relatives, contributes significantly to academic stress.…”
Section: Introductionmentioning
confidence: 99%